Odpowiedź :
Odpowiedź:
a) 12 + x = 51
x = 39
b) 2x - 5 = 87
2x = 82 /:2
x = 41
c) 11 - x = - 5
16 = x
d) 3x + 8 = 20
3x = 12 /:3
x = 4
e) 4x + 3 = - 13
4x = - 16 /:4
x = - 4
f) 3x + 1 = 2x - 7
3x - 2x = - 7 - 1
x = -8
Odpowiedź:
[tex]a)\\\\12+x=51\\\\x=51-12\\\\x=39\\\\\\b)\\\\2x-5=87\\\\2x=87+5\\\\2x=92\ \ |:2\\\\x=46\\\\\\c)\\\\11-x=-5\\\\-x=-5-11\\\\-x=-16\ \ |\cdot(-1)\\\\x=16[/tex]
[tex]d)\\\\3x+8=20\\\\3x=20-8\\\\3x=12\ \ |:3\\\\x=4\\\\\\e)\\\\4x+3=-13\\\\4x=-13-3\\\\4x=-16\ \ |:4\\\\x=-4\\\\\\f)\\\\3x+1=2x-7\\\\3x-2x=-7-1\\\\x=-8[/tex]